Developing Temporal Allocation Profiles for Electric Generating Utilities based on the CleanSYS Real-time Emissions CleanSYS 실시간 배출량을 이용한 발전부문 시간 분배계수 작성 - Bae, Minah; Yoo, Chul; Kim, Hyungcheon; Kim, Soontae (Journal of Korean Society for Atmospheric Environment, 2021)
The bottom-up national emission inventory (EI) in South Korea named the Clean Air Policy Support System (CAPSS) provides annual and monthly emission rates. The EI should be treated for spatial and temporal allocations, and chemical speciation to prepare the hourly resolved emissions prior to air quality assessments. The real-time emission rates for the major point sources in South Korea are continuously monitored by the CleanSYS. We utilized the CleanSYS 1-h emission data for 68 stacks in the electric generating utilities (EGU) to compare the total emissions against those in the CAPSS during 2017 and to develop the temporal allocation profiles for SOx, NOx, PM10, and PM2.5 based on the real-time stack emissions. The total SOx and NOx emissions from the 68 stacks reported in the CAPSS were 4% and 3% respectively lower than the real-time emissions. The differences were mostly due to the underestimation of the emissions from the anthracite-burning facilities. When the annual emissions of 68 stacks were resolved to the monthly, daily, and hourly emissions with the temporal profiles developed in this study, the monthly SOx and NOx emission decreased by 11~21% in winter and increased by 11~26% in summer. The nighttime emission rates increased by up to 48% and the daytime emission rates decreased by up to 16%. The hourly emissions in the CleanSYS can be directly used for the real-time measurement period. However, the temporal allocation profiles developed in this study can be applied to generate typical time-varying emissions for the stacks of which real-time emissions are unavailable or to predict the concentrations of air pollutants in a future year based on the emission growth and control scenarios.
Keywords: CleanSYS; Electric generating utilities; Real-time emissions; Temporal profile; Typical emissions